THE FACTORS INFLUENCING THE INTENTION TO QUIT SMOKING AMONG MILITARY STUDENTS IN THE ROYAL THAI ARMY - Siripukdeekan, Chayaluck; Kasemsuk, Weha (JOURNAL OF THE POLICE NURSES AND HEALTH SCIENCE, 2024)
The objective of this predictive study was to investigate smoking behaviors and the factors influencing the intention to quit smoking among military cadets in the Royal Thai Army. The sample included 481 military students enrolled in educational institutions affiliated with the Royal Thai Army during the 2022 academic year, all of whom were either current smokers or had a history of smoking. Simple random sampling was used to select participants. Data were collected through an online questionnaire comprising 48 items designed to assess factors affecting the intention to quit smoking. The index of item-objective congruence (IOC) was at .67 or higher, and the Cronbach’s alpha coefficient was .907. Analysis of the data involved descriptive statistics and multiple linear regression analysis using the Enter method. Findings revealed that 1) The respondents reported that an average age of initial smoking onset was between 16 and 18 years (49.50%, M = 17.02 years, SD = 2.38). Daily cigarette consumption ranged from 1 to 10 cigarettes (83.60%, M = 5.49 cigarettes/day, SD = 5.75), while smoking durations varied from 2 to 5 years (45.30%, M = 3.74 years, SD = 2.85). Curiosity was identified as the most common reason for smoking (45.70%). The types of cigarettes commonly used included traditional cigarettes alone (39.10%), a combination of traditional and e-cigarettes (34.30%), and solely e-cigarettes (22.90%). The majority of participants smoked on a daily basis (48.20%). Notably, military cadets exhibited high levels of awareness regarding their own attitudes and abilities, social support, and intention to quit smoking, and 2) The study found that variables such as age of first smoking, smoking quantity per day, frequency, duration, social support in smoking cessation, self-efficacy in smoking control, and attitude towards smoking cessation collectively accounted for 63.70 percent of the variance in smoking cessation intention among military cadets in the Royal Thai Army (R = .798, R2 = .637, F (7,473) = 118.785, p = .000). Recommendations include establishing smoking cessation clinics or organizing anti-smoking campaigns in schools, enhancing awareness regarding the adverse effects of e-cigarettes, and providing support resources for individuals seeking to quit smoking.